Comprehensive panel of cross‐reacting monoclonal antibodies for analysis of different immune cells and their distribution in the common marmoset (Callithrix jacchus). Issue 3 (16th May 2016) - Neumann, Berit; Shi, Tingchuan; Gan, Li Lin; Klippert, Antonina; Daskalaki, Maria; Stolte‐Leeb, Nicole; Stahl‐Hennig, Christiane
Abstract: Background: Common marmosets are extensively used in immunological and pharmacological research, and the usage of methods such as flow cytometry gain increasing importance. Methods: Using multicolor flow cytometry cross‐reactivity of monoclonal antibodies with cells of common marmosets was analyzed. Furthermore, frequencies of immune cells and immunological parameters were assessed in healthy common marmosets. Results: A total of 97 clones of monoclonal antibodies raised against CD markers, chemokine receptors, and miscellaneous markers were tested. Additionally, baseline frequencies of different innate and adaptive immune cells as well as certain parameters, such as activation and memory T‐cell and B‐cell distribution, are provided. Conclusion: Our study gives an extended overview of cross‐reactive antibodies for flow cytometric analysis of immune cells as well as baseline values for different immune parameters in healthy common marmosets.